The influence of working environment on well-being and job satisfaction of healthcare providers in geriatric nursing facilities in Shandong Province in China - Hu, Xiaoli; Ren , Ying; Qi , Yan-fei; Chu, Sheng-yong (Pacific International Journal, 2023)
The objective of this cross-sectional study was to examine the relationships between working environment, job satisfaction and subjective well-being. Based on the data gathered from 229 employees in the geriatric nursing facilities in Shandong province in China, 68% of elderly caregivers for the elderly, who were examined using the GWB scale, had scores exceeding 73, which indicates positive well-being. Approximately 57 (34.89%) caregivers reported being dissatisfied with their job.Correlation analyses showed that better working environment had positive effects on employees’ well-being and job satisfaction. Multiple linear regression analysis identified several factors that significantly increased the odds of subjective well-being. This included job satisfaction, the number of seniors you care for and the working environment. Specifically, registered nurses working in geriatric nursing facilities had lower levels of subjective well-being compared with other elderly caregivers.